The Impact of Self-Confidence, Family Support, and Motivation on Entrepreneurial Interest: The Mediating Role of Entrepreneurship Education - Nurhayani Nurhayani; Andika Isma; Soussou Raharimalala (CV. Sakura Digital Nusantara, 2025)
Entrepreneurial interest refers to an individual’s desire to engage in business activities, driven by feelings of enjoyment and perceived personal benefit. Self-confidence represents a person’s belief and positive attitude toward their own abilities, the environment, or anticipated situations. Family support is the assistance provided by family members to help address challenges more effectively. Motivation is a condition that triggers behavior and is closely related to the work environment. Meanwhile, entrepreneurship education serves as a learning platform to enhance knowledge, competence, and the intention to develop one’s entrepreneurial potential. This study aims to examine the direct and indirect effects of self-confidence, family support, and motivation on entrepreneurial interest, with entrepreneurship education acting as a mediating variable. The research employed a quantitative descriptive-explanatory approach and involved 121 respondents selected through proportional random sampling. The findings reveal that self-confidence, family support, and motivation significantly influence entrepreneurial interest both directly and indirectly through entrepreneurship education. These results offer valuable insights for educators to better guide students in developing entrepreneurial skills. Students are encouraged not only to focus on product creation but also to deepen their skills in business management, marketing, and decision-making to support business growth. Future researchers are recommended to further expand this study by exploring additional variables and methodological improvements.